Breast cancer as photodynamic therapy target: Enhanced therapeutic efficiency by overview of tumor complexity - Lamberti, María Julia (World J Clin Oncol, 2014)
Photodynamic therapy is a minimally invasive and clinically approved procedure for eliminating selected malignant cells with specific light activation of a photosensitizer agent. Whereas interstitial and intra-operative approaches have been investigated for the ablation of a broad range of superficial or bulky solid tumors such as breast cancer, the majority of approved photodynamic therapy protocols are for the treatment of superficial lesions of skin and luminal organs. This review article will discuss recent progress in research focused mainly on assessing the efficacies of various photosensitizers used in photodynamic therapy, as well as the combinatory strategies of various therapeutic modalities for improving treatments of parenchymal and/or stromal tissues of breast cancer solid tumors. Cytotoxic agents are used in cancer treatments for their effect on rapidly proliferating cancer cells. However, such therapeutics often lack specificity, which can lead to toxicity and undesirable side effects. Many approaches are designed to target tumors. Selective therapies can be established by focusing on distinctive intracellular (receptors, apoptotic pathways, multidrug resistance system, nitric oxide-mediated stress) and environmental (glucose, pH) differences between tumor and healthy tissue. A rational design of effective combination regimens for breast cancer treatment involves a better understanding of the mechanisms and molecular interactions of cytotoxic agents that underlie drug resistance and sensitivity.